Situation Report: Hungary, 16 March 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. What Is Wrong with the Hungarian National Theater? Film Festival Highlights Problems with Movie Attendance Managers Discuss Current Economic Policy Problems Foreign Trade Situation and Plans for 1979 Work Force Dismissals at the Gyor Wagon and Machine Works Kadar and Brezhnev Emphasize Socialist Unity and Solidarity